Rule based signal processing for ambulatory fetal monitoring - Mohd Ali, Mohd Alauddin; Ibrahimy, Muhammad Ibn; Zahedi, Admond (2004)
An algorithm has been developed for the simultaneous measurement of the fetal and maternal heart rates from the maternal abdominal electrocardiogram during pregnancy and labor. The algorithm is based on digital filtering, adaptive thresholding, statistical properties in the time domain and differencing of local maxima and minima. The technique has been developed through a combination and modification of earlier techniques making it suitable for ambulatory monitoring. Eighteen volunteers at various weeks of gestation were studied for the fetal heart rate detection. The computation complexity is such that the developed algorithm can extract both maternal and fetal heart rates in real-time utilizing a single-lead configuration.